Does a whole plant conservation gradient exist within a subtropical broadleaved evergreen forest? - Fan, Ailian; Wang, Xue; Yan, Xiaojun; Chen, Tingting; Jiang, Qi; Jia, Linqiao; Wang, Weiwei; Xiong, Decheng; Huang, Jinxue; Chen, Guangshui (Frontiers in Plant Science, 2024)
The coordination between leaf and root traits is crucial for plants to synchronize their strategies for acquiring and utilizing above- and belowground resources. Nevertheless, the generality of a whole plant conservation gradient is still controversial. Such testing has been conducted mainly among communities at large spatial scales, and thus evidence is lacking within communities. This is noteworthy because factors that influence leaf and root trait variation differ across scales. Here, we measured pairs of analogous leaf and first-order root traits, including morphological (leaf thickness (LT) and root diameter (RD), leaf mass per unit area (LMA) and specific root length (SRL), and leaf and root tissue density (LTD and RTD)) and chemical traits (carbon (C) and nitrogen (N) concentrations in leaf and root tissues), on the same plants from 60 woody species within a subtropical broad-leaved evergreen forest. The trade-off patterns in and correlations between leaf and root traits were examined using (phylogenetic) principal component analysis and correlation analysis. Our results revealed two dominant dimensions of leaf trait variation, the leaf economics spectrum (LES) and the LT-LTD trade-off axis. Variations in root traits were mainly accounted for by a two-dimensional root economics space (RES) (i.e., root conservation gradient (RTD-RN) and root collaboration gradient (RD-SRL)). The LES and root conservation gradient were correlated and could be integrated into one whole plant conservation gradient, independent of the root collaboration gradient and the leaf LT-LTD trade-off dimension. Leaf and root N concentrations correlated positively, independent of phylogeny, whereas analogous leaf and root morphological traits varied independently of each other. These results support the existence of a whole plant conservation gradient, but also highlight a complex integration of multiple above- and belowground adaptive strategies of plants within a forest community, which offer new insight into ecological trade-offs, species coexistence and community assembly in the forest ecosystem.